Inflammasome activation by viral infection: mechanisms of activation and regulation - Shi, Wen; Jin, Mengyun; Chen, Hao; Wu, Zongxue; Yuan, Liuyang; Liang, Si; Wang, Xiaohan; Memon, Fareed Uddin; Eldemery, Fatma; Si, Hongbin; Ou, Changbo (Frontiers in Microbiology, 2023)
Viral diseases are the most common problems globally, which threaten human beings' health, livestock, and poultry industry. Viral infection is a complex and competitive dynamic biological process between virus and host/target cell. During viral infection, inflammasomes play important roles in host and confer the defense mechanism against virus. Inflammasomes are polymeric protein complexes and considered the important components of innate immune system. These immune factors recognize the signals of cell damage or pathogenic microbial infection after activation by canonical pathway or noncanonical pathway and transmit signals to the immune system to initiate the inflammatory responses. However, some viruses inhibit the activation of the inflammasomes in order to replicate and proliferate in the host. In recent years, the role of activation and/or inhibition of inflammasome has been increasingly recognized during viral infection. Therefore, in this review, we describe the biological properties of the inflammasome associated with viral infection, discuss the potential mechanisms which activate and/or inhibit NLRP1, NLRP3 and AIM2 inflammasomes by different viruses and summarize the reciprocal regulatory effects of viral infection on NLRP3 inflammasome in order to explore the relationship between viral infections and inflammasomes. This review will pave the way to future studies on the activation mechanisms of inflammasomes and provide novel insights toward the development of antiviral therapies.